Assessment of the reliability and validity of simple and complex reaction speed tests in mixed martial arts athletes using the BlazePod system - Polechonski, J.; Pilch, J.; Langer, A.; Pronczuk, M.; Markowski, J.; Maszczyk, A. (Baltic Journal of Health and Physical Activity, 2025)
The main aim of the research was to evaluate the reliability and validity of measurements of simple and complex reaction speed using the BlazePod system in MMA athletes. Additionally, these motor skills for the right and left hands of the studied athletes were compared. The study involved 34 male professional MMA practitioners (training experience 7.0±4.0 years, age 26.5±5.3 years, body mass 76.9±9.8 kg, height 178.5±5.7 cm). The evaluation of reaction speed utilized the BlazePodTM system and classic computer tests. The time from the activation of a light stimulus to the hand striking a glowing target in front of the participants was assessed. Measurement reliability was estimated based on the intraclass correlation coefficient (ICC). Correlation analysis was employed to assess the validity of the BlazePod tests. It was found that ICC values for reaction speed tests performed using the BlazePod system were slightly higher than those for computer tests. For simple reactions of the right and left upper limb, ICC values were similar at 0.826 and 0.833, respectively. In the complex reaction test, the ICC value was slightly lower (ICC = 0.785). The correlation of test results using the BlazePod system and computer tests was high: right hand (r = 0.703; p < 0.001), left hand (r = 0.654; p < 0.001), complex reaction (r = 0.640; p < 0.001). The ICC analysis indicates that the simple and complex reaction speed tests performed by MMA athletes using the BlazePod system demonstrate good reliability, and their results strongly correlate with those of classic computer tests. Therefore, the BlazePod light system can be considered a measurement tool allowing for a reliable and valid assessment of the simple and complex reaction speed of MMA athletes.